PENGEMBANGAN LEMBAR KEGIATAN SISWA BERBASIS PROBLEM BASED LEARNING (PBL) PADA MATERI SISTEM PENCERNAAN MANUSIA DI SMA KELAS XI - NOVIYANTI, EKA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2014)
Digestive system is one of the material that must be comprehended by students grade XI. For this matter would be simply understand by students, it is should added experiment activity in learning process on matter human digestive system. In general experiment activity on matter human digestive is food contens test like carbohydrate, lipid, and protein. Learners are given a different experience from the usual practice. It required another practical alternative to the digestive system, such as formalin test and test caffeine levels. The objectives of this research is to produce and to described the theoritical feasibility of student worksheet. This research conducted based on Four-D (4-D) development methods. The result of this research indicates that developed student worksheets based on problem based learning on the matter human digestive system as learning media could be declared feasible with worksheets validation 97%. Keywords: student worksheet, problem based learning, digestive sistem.